Skinnytaste air fryer dinners : 75 healthy recipes for easy weeknight meals - Homolka, Gina; Jones, Heather K (Clarkson Potter/Publishers, 2021)
"75 recipes dedicated to making air fryer dinners easier and healthier, from the #1 New York Times bestselling author of The Skinnytaste Air Fryer Cookbook. In Skinnytaste Air Fryer Dinners, Gina Homolka delivers 75 air fryer meals that are the perfect quick solution to weeknight meals, hearty dinners that are satisfying served as is or with just a simple salad or side. True to Gina's signature "light on calories, big on flavor" promise, her new recipes allow you to indulge in creative and crave-worthy dishes, including Catfish and Hushpuppies with Creamy Slaw, Chicken-Fried Steak with Sage Gravy, Blackened Fish Tacos, Giant Samosas with Cilantro-Mint Chutney, and Fried Shrimp Po-Boy Wrap. All recipes include helpful icons for different diets (such as gluten-free and vegetarian) and nutritional information, with the most up-to-date Weight Watchers points available on the Skinnytaste website"--